Prototype of Microcontroller Based Water Pump Control System for Lettuce Plants Using Fuzzy Tsukamoto - Rifansyah, Mhd. Roji; R, Rakhmat Kurniawan (Newinera Publisher, 2024)
This research aims to design and implement a water pump control system for lettuce plants using a microcontroller based on the Tsukamoto fuzzy method. The system utilizes soil moisture sensors and DHT11 temperature sensors to monitor and control the water supply for optimal plant growth. The fuzzy logic control involves three stages: fuzzification, rule evaluation, and defuzzification. Experimental results demonstrate the system's effectiveness in maintaining the desired soil moisture levels, thus ensuring optimal conditions for lettuce plant development. The prototype includes components such as Arduino Uno, relays, water pumps, and LCD displays, all of which integrate seamlessly to achieve the desired control outcomes. The study concludes that the designed system can significantly aid in automating water supply processes, thus benefiting small-scale agricultural practices.